2002
DOI: 10.1007/s00259-002-0919-x
|View full text |Cite
|
Sign up to set email alerts
|

Value of 99mTc-ECD SPET for the diagnosis of dementia with Lewy bodies

Abstract: Despite improved diagnostic accuracy, differentiation of dementia with Lewy bodies (DLB) and Alzheimer's disease (AD) on the basis of clinical findings remains problematic. The purpose of this retrospective study was to evaluate the utility of technetium-99m ethyl cysteinate dimer (ECD) single-photon emission tomography (SPET) as a potential tool for the diagnosis of DLB and discrimination from AD. Cerebral perfusion patterns detected by (99m)Tc-ECD SPET were compared in patients presenting with a probable dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 31 publications
3
73
4
Order By: Relevance
“…The studies showed a variable DLB sensitivity and AD specificity of 65% to 85% and 71% to 87%, respectively. 10,11,13,14,33 Studies using 18 F-fluorodeoxyglucose positron emission tomography have largely shown greater diagnostic accuracy than perfusion SPECT in distinguishing DLB from AD. 34,35 The DLB sensitivity and AD specificity are quoted as ranging from 86% to 92% and from 80% to 92%, respectively, although such results should be viewed with caution because of the relatively small samples studied and indeed larger more recent AD DLB positron emission tomography study was found to be less accurate (sensitivity 64%, specificity 65%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies showed a variable DLB sensitivity and AD specificity of 65% to 85% and 71% to 87%, respectively. 10,11,13,14,33 Studies using 18 F-fluorodeoxyglucose positron emission tomography have largely shown greater diagnostic accuracy than perfusion SPECT in distinguishing DLB from AD. 34,35 The DLB sensitivity and AD specificity are quoted as ranging from 86% to 92% and from 80% to 92%, respectively, although such results should be viewed with caution because of the relatively small samples studied and indeed larger more recent AD DLB positron emission tomography study was found to be less accurate (sensitivity 64%, specificity 65%).…”
Section: Discussionmentioning
confidence: 99%
“…Using region of interest methods, occipital, frontal, and parietal lobe perfusion deficits have been observed in DLB relative to AD, with relative preservation of temporal lobe perfusion. [9][10][11] Using voxelwise procedures, reduced rCBF in occipital cortex as well as in the precuneus has been shown in DLB compared with AD. [12][13][14] Results from visual rating are less consistent, 15,16 with some even reporting similar patterns of hypoperfusion between DLB and nonDLB cases.…”
Section: Introductionmentioning
confidence: 99%
“…Pasquier et al, 18 who used 99m Tc-labelled ethylcysteinate dimer as a tracer in their brain perfusion SPECT study, found that the sensitivity for the diagnosis of DLB was 65% and specificity was 71%. Similarly, each hypoperfusion of the posterior cingulate, praecuneus and occipital lobe was a meaningful index in the univariate analysis in our study.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17] The value of 123 I-MIBG myocardial scintigraphy in the early diagnosis of DLB and in the differential diagnosis between DLB and other dementias has been studied; scintigraphic findings are reported to yield independent diagnostic predictors of DLB. [18][19][20][21] In their metaanalysis, Treglia and Cason 22 demonstrated that MIBG scintigraphy is an accurate diagnostic imaging method to differentiate DLB from other dementias; they reported a pooled sensitivity and specificity of 98% and 94%, respectively. In addition, 123 I-MIBG scintigraphy appears to be of higher sensitivity than brain perfusion SPECT for the diagnosis of DLB.…”
Section: Resultsmentioning
confidence: 99%
“…Perfusion SPECT studies (see Table 3) have assessed regional cerebral blood flow, a marker of brain function, using 99m Tc-hexamethylpropylene amine oxime (HMPAO), 13,26-29 99m Tc-ethyl cysteinate dimer (ECD) 13,16,30 AD. Combining these two measures gave good sensitivity of 95% and modest specificity of 65% (see Table 3).…”
Section: Cerebral Perfusion Imagingmentioning
confidence: 99%